THE AESTHETICS OF SENAPATI PINILIH, A KETOPRAK STORY BY BONDAN NUSANTARA - Sumaryadi, Sumaryadi (LITERA, 2018)
This study aims to describe the aesthetics of Senapati Pinilih, a ketoprak (Javanese play) story by Bondan Nusantara. The material object of the study is the story and the formal object is its philosophy of beauty or aesthetics. The ketoprak story is an integral part of the ketoprak art. The aesthetics of Senapati Pinilih is approached by Monroe Beardsley’s theory in his book Aesthetics: Problems in the Philosophy of Criticism that explains that there are three characteristics of the good or beautiful nature of aesthetic objects, namely unity, complexity, and intensity. The data were collected through observations, in-depth interviews, and documentation study. They were analyzed through the stages of data reduction, data classification, and data display, and by the methods of verstehen, interpretation, language analysis, and heuristics. The findings are as follows. Aesthetics has integrated patterns and forms, especially for the characters in Senapati Pinilih, and serves as markers of the story atmosphere. In this story, Bondan Nusantara wraps the theme, dialog media, directions of motion and behavior into a unified whole. With an unconventional plot Bondan Nusantara makes this story complex, rich in contents and mutually contrary elements. In this story, Bondan Nusantara structures the story dynamically, not monotonously, so that the concentration or attention of the readers (or viewers) can be maintained throughout the progress of the story. Serious nuances are proportionately and effectively combined with humorous ones. Keywords: ketoprak story, aesthetics, character education ESTETIKA SENAPATI PINILIH, SEBUAH CERITA KETOPRAK OLEH BONDAN NUSANTARA Abstrak Penelitian ini bertujuan mendeskripsikan estetika Senapati Pinilih, sebuah cerita ketoprak (Jawa) oleh Bondan Nusantara. Objek material penelitian adalah cerita dan objek formal adalah filosofinya tentang keindahan atau estetika. Cerita ketoprak merupakan bagian integral dari seni ketoprak. Estetika Senapati Pinilih diteliti dengan pendekatan teori Monroe Beardsley dalam bukunya Aesthetics: Problems in the Philosophy of Criticism yang menjelaskan bahwa ada tiga karakteristik dari sifat baik atau keindahan objek estetika, yaitu kesatuan, kompleksitas, dan intensitas. Data dikumpulkan melalui observasi, wawancara mendalam, dan studi dokumentasi. Data dianalisis melalui tahap-tahap pengurangan data, klasifikasi data, dan tampilan data, dan dengan metode verstehen, interpretasi, analisis bahasa, dan heuristik. Temuan penelitan sebagai berikut. Estetika memiliki pola dan bentuk yang terintegrasi, terutama untuk karakter dalam Senapati Pinilih dan berfungsi sebagai penanda suasana cerita. Dalam cerita ini, Bondan Nusantara membungkus tema, media dialog, arah gerak, dan perilaku menjadi satu kesatuan yang utuh. Dengan plot yang tidak konvensional, Bondan Nusantara membuat cerita ini kompleks, kaya isi, dan unsur-unsur yang saling bertentangan. Dalam cerita ini, Bondan Nusantara menyusun cerita secara dinamis, tidak monoton, sehingga konsentrasi atau perhatian para pembaca (atau pemirsa) dapat dipertahankan sepanjang perkembangan cerita. Suasana serius dikombinasikan dengan humor secara proporsional dan efektif.Kata kunci: cerita ketoprak, estetika, pendidikan karakter